Cultivation systems in plum orchards - Gonda, I. (International Journal of Horticultural Science, 2007)
In this review, we give an overview of recent cultivation systems in commercial plum orchards. The aspects of selecting the shape of the crown and the spacing of trees are discussed first and then growth characteristics and the structure of the crow are described in detail. Finally, the wound healing and regeneration characteritics of plum trees are detailed which have an influence on the applied pruning technique.